Revisiting Lemma Lists in Swahili Dictionaries - Wójtowicz, Beata (Lexikos, 2017)
When compiling a dictionary, a lexicographer has a set of decisions to make — starting with drawing up a lemma list to such issues as formatting a dictionary entry. Relying on corpus data while designing a lemma list and describing entries is standard in present lexicography, but there are still decisions — like the choice of a lemma or how to treat derivatives — that are often intuition-based. This article aims to investigate whether decisions put forward in Swahili dictionaries comply with users' expectations. We analyse log files from the new Swahili–Polish dictionary to investigate why looking up words goes wrong, and evaluate the choice of a lemma and the treatment of derivatives in Swahili dictionaries. Based on such data we intend to expand or modify the existing electronic dictionary to adapt to users' level of grammar and dictionary structure knowledge. During this research we identified a list of lemma lacuna that cause the majority of unsuccessful Swahili searches. The study shows that users know and understand the lemmatisation strategy of the dictionary but also reveals which word forms cause the most problems and how the lemma list of Swahili dictionaries could be expanded.